2017
DOI: 10.35188/unu-wider/2017/388-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective corporate tax burden and firm size in South Africa: A firm-level analysis

Abstract: We investigate the relationship between the corporate income tax burden and firm size in South Africa using a panel dataset from companies' tax returns. We find that medium-sized companies are experiencing the lowest effective tax rate, while the smallest companies are facing the highest effective tax rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
1
10
0
5
Order By: Relevance
“…In some foreign countries, the effective (actual) tax rate, which represents the share of tax in the total taxable income of the taxpayer, is used to estimate the tax burden. The results of the study of the relationship between the effective tax rate and the size of the company allow us to assess the quality of tax regulation [8,9,10], including the investment aspect [11,12,13,14]. Attention is drawn to the lack of a relationship between corporate tax rates and foreign investment of companies [15,16].…”
Section: Analysis Of Methods For Assessing the Tax Burden Of Organizationsmentioning
confidence: 99%
“…In some foreign countries, the effective (actual) tax rate, which represents the share of tax in the total taxable income of the taxpayer, is used to estimate the tax burden. The results of the study of the relationship between the effective tax rate and the size of the company allow us to assess the quality of tax regulation [8,9,10], including the investment aspect [11,12,13,14]. Attention is drawn to the lack of a relationship between corporate tax rates and foreign investment of companies [15,16].…”
Section: Analysis Of Methods For Assessing the Tax Burden Of Organizationsmentioning
confidence: 99%
“…The findings of the World Bank are backed up by the OECD (Hanappi 2018), which found that METRs in South Africa showed significant variation across asset types, although this report assumed inflation of 0.73 and 2 per cent-both much lower than the current reality in South Africa, where inflation has fluctuated between around 4 and 7 per cent over recent years-and either full debt or full equity financing. Carreras et al (2017) found that the effective tax burden varied across firm size in South Africa, with medium-sized firms facing the lowest and small firms the highest effective tax rates.…”
Section: Institutional Settingmentioning
confidence: 98%
“…Penelitian Rodriguez, Fernandez, dan Arias (2019) menunjukkan hasil bahwa perusahaan-perusahaan besar memiliki ETR yang lebih rendah, karena memilliki alokasi sumber daya yang lebih besar untuk strategi perpajakan untuk mengurangi perpajakan. Penelitian itu didukung oleh penelitian lainnya (Carreras et al, 2017;Rani et al, 2018;Setiawan & Al-ahsan, 2016) yang menemukan hasil serupa. Berdasarkan teori dan penelitian sebelumnya, dapat diketahui jika ukuran perusahaan merupakan faktor yang dapat mempengaruhi nilai ETR.…”
Section: Ukuran Perusahaanunclassified